Effect of Lactic Acid Supplementation on the Growth and Reproduction of Bombyx mori (Lepidopteria: Bombycidae). Issue 2 (25th March 2021) - He, Zhen; Fang, Yang; Li, De-Chen; Chen, Deng-Song; Wu, Fan
Abstract: Lactic acid is widely used in the food, drugs, cosmetics, and other industries to maintain the microbial stability of low-pH products. However, it is unclear whether lactic acid can affect silkworm ( Bombyx mori ) growth and reproduction. This study investigated the effects of lactic acid on the growth and reproduction of the silkworm. We analyzed the growth, cocoon quality, and reproductive performance of fifth instar larvae fed on mulberry leaves saturated with different concentrations (0.01, 0.1, 1, and 10%) of lactic acid and the control. Results showed that 0.01, 0.1, and 1% lactic acid supplementation positively affects growth and female cocoon quality, with increased larval weight and female cocoon shell weight compared to the control group. In contrast, 10% lactic acid was toxic to the larvae and significantly decreased growth, leading to larval death. Our study provides a basic reference for the optimal amount of preservatives. In addition, this study can be a desirable intervention for sericulturists and can play an important role in getting high return from silkworm-rearing activities.